Трансформація позицій політичних партій ФРН щодо східноєвропейської політики (2005-2017 рр.) - Харлан, Г. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті досліджено концептуальні підходи німецьких політичних
партій щодо перспектив взаємодії зі східноєвропейськими державами у
2005–2017 рр. Позиції політичних сил ФРН охарактеризовані за ступенем впливу тієї чи іншої партії на перебіг політичного життя.
Проаналізовано зовнішньополітичні пріоритети східноєвропейської політики шести основних партій (ХДС/ХСС, СДПН, ВДП, «Союз 90/Зелені»,
«Ліві», «Альтернатива для Німеччини») під час урядування другої «великої», християнсько-ліберальної, та третьої «великої» коаліцій на чолі з федеральним канцлером А. Меркель. У висновках зазначається, що Революція Гідності, підписання Угоди
про асоціацію, анексія Криму та війна на Сході України засвідчили необхідність перегляду зовнішньополітичних орієнтацій щодо східноєвропейської політики та розробки принципово нових форм взаємодії Німеччини
зі східноєвропейськими державами. Певною мірою ця тенденція відобразилася в програмних документах та полеміці напередодні виборів до
Бундестагу 2017 р. The article researches conceptual approaches of the German political
parties regarding the prospects of interaction with the Eastern European states
in 2005–2017. Positions of political forces of the Federal Republic of Germany
are characterized by the degree of impact of one or another party to the course
of political life. The priorities in the Eastern European policy of the six main
parties (CDU/CSU, SPD, FDP, “Alliance 90/The Greens”, “Left”, “Alternative
for Germany”) during the reign of the second “grand” Christian-liberal
coalition, and the third “grand” coalition led by Federal Chancellor A. Merkel
are analysed.
Almost all political forces stood for Germany’s active participation in the
process of European integration. Instead, there were significant differences in
the issue of relations between Germany and the Eastern European states and
prospects of their joining the European Union. The CDU/CSU position was
based on solving traditional problems of maximum security in Europe. The
SPD strategy was based on the fact that Russia, as well as during the
confrontation between blocks in the Cold War, should be the nucleus of the
East European policy of the FRG. The views of the FDP in general are in line
with the positions of the CDU / CSU. The “Alliance 90/The Greens” stressed
the need for a pan-European security system and the further implementation of
the European Neighbourhood Policy. The rhetoric of the “Left” and the representatives
of the “Alternative for Germany” party was plainly pro-Russian.
The author concludes that the Revolution of Dignity, the signing of the
Association Agreement, the annexation of Crimea and the war in the East of
Ukraine have shown the need for a revision of orientations in the Eastern
European politics and the development of fundamentally new forms of interaction
between Germany and the Eastern European states. To a certain extent,
this trend has been reflected in the program documents and polemics on the
eve of the Bundestag 2017 elections.